Cancer Immunotherapy: A Review - Anna Meiliana; Nurrani Mustika Dewi; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2016)
BACKGROUND: The goals of treating patients with cancer are to cure the disease, prolong survival, and improve quality of life. Immune cells in the tumor microenvironment have an important role in regulating tumor progression. Therefore, stimulating immune reactions to tumors can be an attractive therapeutic and prevention strategy.CONTENT: During immune surveillance, the host provides defense against foreign antigens, while ensuring it limits activation against self antigens. By targeting surface antigens expressed on tumor cells, monoclonal antibodies have demonstrated efficacy as cancer therapeutics. Recent successful antibody-based strategies have focused on enhancing antitumor immune responses by targeting immune cells, irrespective of tumor antigens. The use of antibodies to block pathways inhibiting the endogenous immune response to cancer, known as checkpoint blockade therapy, has stirred up a great deal of excitement among scientists, physicians, and patients alike. Clinical trials evaluating the safety and efficacy of antibodies that block the T cell inhibitory molecules cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) and programmed cell death 1 (PD-1) have reported success in treating subsets of patients. Adoptive cell transfer (ACT) is a highly personalized cancer therapy that involve administration to the cancer-bearing host of immune cells with direct anticancer activity. In addition, the ability to genetically engineer lymphocytes to express conventional T cell receptors or chimeric antigen receptors has further extended the successful application of ACT for cancer treatment.SUMMARY: For cancer treatment, 2011 marked the beginning of a new era. The underlying basis of cancer immunotherapy is to activate a patient’s own T cells so that they can kill their tumors. Reports of amazing recoveries abound, where patients remain cancer-free many years after receiving the therapy. The idea of harnessing immune cells to fight cancer is not new, but only recently have scientists amassed enough clinical data to demonstrate what a game-changer cancer immunotherapy can be. This field is no stranger to obstacles, so the future looks very promising indeed.KEYWORDS: immune checkpoint, adoptive cell transfer, neoantigen, monoclonal antibody